Estimation of Genetic Parameters of Different Wheat Genotype Traits in Chitwan, Nepal - Saroj Regmi; Bikram Poudel; Bishnu Raj Ojha; Raju Kharel; Priyanka Joshi; Shovit Khanal; Bishnu Prasad Kandel (International Journal of Agronomy)
This research was carried out to estimate the genetic parameters of fifty wheat genotypes received from the Agriculture Botany Division, Nepal Agriculture Research Council (NARC), Khumaltar, Lalitpur, in the winter season of 2014/2015 at Agriculture and Forestry University (AFU), Chitwan, Nepal. The experiment was performed in an alpha lattice design with two replications in five blocks in each replication and ten plots in each block. The analysis of variance showed highly significant differences among the genotypes for all the studied traits except spike length. This implies that, except for spike length, all other traits exhibited genetic variability. The phenotypic coefficient of variation (PCV) was generally higher than the genotypic coefficient of variation (GCV) for all characters. The difference between PCV and GCV was large in spike length followed by grain weight per spike, the number of grains per spike, grain yield, thousand-grain weight, and harvest index indicating that these traits are affected by the environment as well. Moderate to high heritability associated with a high genetic gain was observed for days to flag leaf appearance, panicle length, thousand-grain weight, grain yield, and harvest index indicating the involvement of additive gene action. Grain weight per spike, number of grains per spike, thousand-grain weight, biological yield, and harvest index were significantly correlated with grain yield indicating their important contribution to grain yield. WK 2525, WK 2437, and WK 2506 were three promising genotypes in terms of grain yield.